Neutralization of alpha, gamma, and D614G SARS‐CoV‐2 variants by CoronaVac vaccine‐induced antibodies. Issue 1 (8th September 2021) - Fernández, Jorge; Bruneau, Nicole; Fasce, Rodrigo; Martín, Héctor San; Balanda, Monserrat; Bustos, Patricia; Ulloa, Soledad; Mora, Judith; Ramírez, Eugenio
Abstract: Vaccination generates a neutralizing immune response against SARS‐CoV‐2. The genomic surveillance is showing the emergence of variants with mutations in spike, the main target of neutralizing antibodies. To understand the impact of these variants, we report the neutralization potency against alpha, gamma, and D614G SARS‐CoV‐2 variants in 44 individuals that received two doses of CoronaVac vaccine, an inactivated SARS‐CoV‐2 vaccine. Plasma samples collected at 60 days after the second dose of CoronaVac were analyzed by the reduction of cytopathic effect in Vero E6 cells with the three infectious variants of SARS‐CoV‐2. Plasma showed lower neutralization with alpha (geometric mean titer [GMT] = 18.5) and gamma (GMT = 10.0) variants than with D614G (GMT = 75.1) variant. Efficient neutralization against the alpha and gamma variants was not detected in 31.8% and 59.1% of plasma, respectively. These findings suggest the alpha and gamma variants could escape from neutralization by antibodies elicited by vaccination. Robust genomic and biological surveillance of viral variants could help to develop effective strategies for the control of SARS‐CoV‐2.